Afghanistan : Public Financial Management and Accountability Assessment - World Bank (Washington, DC, 2014)
This document reports on a public financial management performance assessment (PFMPA) for the Government of Afghanistan (GoA). The assessment was conducted with the particular objective of updating the PFMPA published in June 2008 to provide the GoA with an objective, indicator led assessment of the public financial management (PFM) system in a concise and standardized manner, to form an updated understanding of the overall fiduciary environment of the PFM system, and to assist in identifying those areas in need of further reform and development. The assessment provides a common information pool with establishment of new baselines against which further progress in PFM development can be assessed. The scope of the assessment is the on-budget activities of the national level budget entities. For the purposes of this report, on budget refers to all operations, including donor financed programs and project financing, and their intended use, which are under the full control of the GoA and are reported in the budget documentation. This is comprehensive of most of Afghanistan's general government sector financial operations since most general government sector revenue and expenditure is on budget and, as a unitary state, there are no provincial governments, while municipalities have very limited service provision responsibilities and resource. This assessment report is structured as follows: chapter one gives introduction; chapter two provides country background and contextual information with regard to the economic situation as well as the legal and institutional framework supporting PFM; chapter three provides the detailed analysis of the 28 GoA related and three donor related performance indicators; and chapter four provides a brief description of the GoA's PFM reform process in recent years and the current PFM reform agenda.